The Time of Enlightenment : Constructing the Future in France, 1750 to Year One - Nelson, William Max, 1976- (Book collections on Project MUSE., 2021)
"In this manuscript, the author demonstrates how a new idea of the future came into being in eighteenth-century France with the development of modern biological, economic, and social engineering. With the emergence of these practices, the future transformed from something that was largely believed to be predetermined and beyond significant human intervention into something that could be significantly affected through actions in the present. Focusing on the second-half of the century, The author argues that specific mechanisms for constructing the future first arose through the development of practices and instruments aimed at countering degeneration. In their attempts to regenerate a healthy natural state, Enlightenment philosophes created the means to exceed previously recognized limits and create a future that was not merely a recuperation of the past, but was fundamentally different from it. The new active orientation to the future that emerged from these practices was not something that was explicitly articulated during the Enlightenment. Instead this practical orientation must be seen as an implicit understanding of historical temporality. Historical actors often had a tacit knowledge of time--one that they worked with--without necessarily being fully aware of it or articulating it explicitly in their writing. The full articulation of the new idea of the future did not occur until the French Revolution, but the practical understanding of it that developed during the Enlightenment played an important role in making possible the French revolutionaries' unprecedented attempts to remake the world completely anew."--